Effects on Light Efficiency in Discharge and Solid-State Lighting Operation, Supplied by No-Sinusoidal Voltage - Clerice, G. A. M. [UNESP]; Castro, B. de [UNESP]; Ulson, J. A. C. [UNESP]; Andreoli, A. L. [UNESP]; Silva Filho, N. M. da [UNESP]; Riehl, R. R. [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2016)
The widespread use of discharge lamps and solid-state lighting is justified by its high-energy efficiency. However, the massive use causes degradation of power quality provided. In this context, the objective was the evaluation and discussion of the effect of harmonic voltage distortion (THDv) in view of the electrical system electrical operation of discharge lamps and solid state. More specifically, they were tested lamps of various types available in Brazil and evaluated rate of harmonic distortion current (THDI), current crest factor (CF), power factor (PF), luminance and bulb temperature before Feeds distorted with THDv 0%, 12.6%, 14.4% and analyzed the effects on brightness and bulb temperature. The results showed that compact fluorescent lamps are the most sensitive to distorted power while the lamps for use in street lighting with magnetic ballasts are the least sensitive.
Keywords: Electroluminescent devices; Lighting; Power conversion; Power quality; Total harmonic distortion